“MAGIC” REALISM OF YEVHEN HUTSALO’S PROSE - Maftyn, N. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
On the material of the collection «Spivucha kolyska z verbolozu» («The Singing Cradle from the Bay Willow») the article analyses the peculiarities of Yevhen Hutsalo’s individual-authorial style, particularly the rootage of his imagery in the archetypal foundation. The fictional world of the collection arises as a concentric model that forms itself around the image of a cottage (khata) and “the tree of life”. The vertical and horizontal of this model are united by the leitmotif image-symbol of the “singing cradle” arising as an all-defeating life-affirming dominant in the ideological-fictional dimension of the collection. With the brightly original style palette and the high truth of life Yevhen Hutsalo’s creativity represents Ukrainian literature in the discourse of “magic realism” as a paradigm of cultural-fictional consciousness of the present time.